COMPARISON FOR SPEECH CODING ALGORITHMS FOR TOTAL LARYNGECTOMIES - AKDENİZ, Rafet; OKTAY, Mesut (MATTER: International Journal of Science and Technology, 2017)
Electrolarynx is used as a noninvasive supporting device for speech restoration in people who have undergone resection operation over their larynxes. This work aims to develop a signal processing method to neutralize the mechanical vibration noise of this device. We investigate the effect of this noise on the speech signal and analyze the performances of various algorithms in a single input system to minimize this noise.